Teaching for mathematical competence: the different foci of modelling competency and problem solving competency - Højgaard, Tomas (2021)
In this article, I argue that it is opportune to work with students’ (mathematical) modelling competency and (mathematical) problem solving competency as two essentially different learning objectives. Such a distinction can be used to facilitate communication when establishing a general agenda in and around the classroom, and especially when developing and/or selecting suitable challenges for students. I begin by outlining what characterises the two competencies. I then highlight core differences, both at an abstract and more concrete level, by analysing how various types of exemplary student tasks can be formulated. Finally, I briefly discuss some of my own experiences when using the presented analytical approach in research and development projects and point towards possible avenues for future research, development, and debate by drawing up two hypotheses concerning which types of tasks dominate compulsory mathematics education and why.